Kontroversi Pemanggilan Arwah dalam Alkitab : Perspektif Teologi Kristen terhadap Kisah Raja Saul dan Samuel - Januar Efendi Sirileleu; Nengris Seko; Malik Bambangan (Pusat Riset dan Inovasi Nasional, 2025)
This paper examines the story of King Saul seeking help from a medium in Endor as a tragic illustration of the spiritual downfall of a leader who was once chosen and anointed by God. In his distress and desperation, Saul chose a path that violated the law, marking his disconnection from God. This action not only shows a serious spiritual deviation, but also reveals the irony that a female medium becomes a means for God to deliver His judgment. It also explores Christian theological views on the practice of séances, including the moral and spiritual implications they bring. By comparing the historical and cultural background of Israel, and reviewing it from a biblical perspective, this paper emphasizes the importance of obedience to God's word and the dangers of involvement in the occult. The relevance of this story to the Christian life today serves as a reminder to remain steadfast in God's revelation and to distance ourselves from deviant spiritual practices. It also invites readers to reflect on the importance of maintaining spiritual integrity in facing the challenges of life.